CD36 expression in peripheral blood mononuclear cells reflects the onset of atherosclerosis - SÖZEN, AHMET ERDİ; YILMAZ, BETÜL; KARTAL ÖZER, NESRİN (WILEY, 2018)
Together with complex genetic and environmental factors, increased serum cholesterol and ox-LDL levels are considered as major triggering factors of atherosclerosis. Mononuclear cell infiltration to the arterial wall and uptake of ox-LDL, which is facilitated by CD36 receptor through an uncontrolled manner, play a key role in foam cell formation followed by atherogenesis development. The aim of this study was to analyze if CD36 expression in peripheral blood mononuclear cells reflect its aortic tissue level in hypercholesterolemia. In this study, CD36 protein expression was evaluated in aortic specimens of cholesterol or cholesterol plus Vitamin E treated animals in relation to the immunohistochemical analyses for the HNE-protein adducts, as well as for smooth muscle actin and vimentin. The CD36 mRNA expression was determined by RT-PCR in PBMC of hypercholesterolemic rabbits and hypercholesterolemic versus normocholesterolemic individuals. Immunohistochemistry findings revealed that smooth muscle actin, smooth muscle vimentin, HNE-protein conjugates, and CD36 protein expressions were significantly increased in aorta of hypercholesterolemic group where foam cells were present. High cholesterol diet significantly induced CD36 mRNA expression in both rabbit aorta and PBMCs, while positive correlation between aortic and PBMC CD36 expression has been found. In addition, consistent with the rabbit model, CD36 mRNA expression levels in human PBMCs were significantly higher in hypercholesterolemic patients than in normocholesterolemic individuals. Taken together, these results demonstrate that the CD36 mRNA levels of PBMCs could reflect the CD36 mRNA levels in aorta and could be used as a biomarker for diagnosis of atherosclerotic burden. (c) 2018 BioFactors, 44(6):588-596, 2018
Keywords: hypercholesterolemia; atherosclerosis; PBMC; CD36 receptor; SCAVENGER RECEPTOR EXPRESSION; VITAMIN-E; OXIDATIVE STRESS; SOLUBLE CD36; OXIDIZED LDL; CARDIOVASCULAR-DISEASE; INSULIN-RESISTANCE; REDOX REGULATION; LIPID RAFTS; CHOLESTEROL